TINJAUAN PROSEDUR PENGELUARAN KAS ATAS REIMBURSEMENT PADA PT OPER BISNIS INDONESIA - Annisa Safitri, (2021)
The final assignment report aims to find out how the procedure for cash disbursement for reimbursement in PT Oper Bisnis Indonesia and has a specific purpose as a requirement for graduation from the Accounting Study Program, the Diploma Three (III) Departement, Veteran National Development University Jakarta. PT Oper Bisnis Indonesia is a startup company that offers a technology-based marketplace. The processing of the data used in the flowchart for this procedure is based on interviews with each of the departments involved in cash disbursements for reimbursements. This cash disbursement procedure for reimbursement is needed to find out the flow of activities of a company's cash disbursement activities arising from the purchase of goods or services as company expenses using employee personal funds after which it will be replaced by company funds through reimbursement submissions. The conclusion of this final project report provides information about the related functions of each chart, the documents used in cash disbursements, and the cash disbursement procedure for reimbursement at PT Oper Bisnis Indonesia has been running well and according to the theory in the procedure.